2019
DOI: 10.1213/ane.0000000000004033
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Modulation as a Target for Chronic Pain: From the Bench to the Bedside and Back

Abstract: With a widespread Opioid Epidemic and profound biopsychosocial implications, chronic pain is a multi-faceted public health issue requiring urgent attention. The treatment of chronic pain is particularly important to anesthesiologists given our unique role as perioperative physicians and pain medicine specialists. The present review details the recent shift from a neuronal theory of chronic pain to one that includes complex neuron-glia interactions. In particular we highlight microglia, the myeloid-lineage cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 123 publications
(141 reference statements)
0
48
0
Order By: Relevance
“… 1 , 20 , 54 Attenuation of neuroinflammation, through inhibition of microglial activation, targeting of specific microglial genes, or selective depletion of spinal microglia, relatively consistently reverses pain hypersensitivity. 25 , 35 …”
Section: Introductionmentioning
confidence: 99%
“… 1 , 20 , 54 Attenuation of neuroinflammation, through inhibition of microglial activation, targeting of specific microglial genes, or selective depletion of spinal microglia, relatively consistently reverses pain hypersensitivity. 25 , 35 …”
Section: Introductionmentioning
confidence: 99%
“…involved in the pathogenesis of chronic pain due to their contributions to neuroinflammation and the resulting alternations in neuronal functions. [4][5][6] Following stimulation, ascending somatosensory signals are generally transmitted from periphery, via the spinal cord, to higher brain regions such as thalamus and cortex. The spinal cord dorsal horn acts as the first relay for ascending somatosensory transmission.…”
mentioning
confidence: 99%
“…Studies in animal models of neuropathic pain have demonstrated that activated spinal microglia (Tsuda et al, 2008) release pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) and lead to phosphorylation of the mitogen-activated protein kinases (MAPKs) including p38-MAPK, extracellular signal-regulated protein kinase (ERK), and c-Jun N-terminal kinase (JNK), which are known to participate in central sensitization and generation of pain hypersensitivity (Obata and Noguchi, 2004; Wang et al, 2014). A recently emerging approach in drug discovery, for diseases characterized by underlying neuroinflammation, is therefore the modulation of microglial polarization and selective regulation of the release of pro-/anti-inflammatory molecules (Haight et al, 2019). This could represent a promising new pharmacological strategy for treatment of chronic pain but also of other disorders such as chronic pain-associated affective disorders and depression (Benatti et al, 2016; Pena-Altamira et al, 2016; Du et al, 2017; Barcelon et al, 2019).…”
Section: Neuroinflammation and Microglial Activation In The Pathophysmentioning
confidence: 99%